Immunochromatographic test for the detection of SARS-CoV-2 in saliva. Issue 2 (February 2021) - Kashiwagi, Katsuhito; Ishii, Yoshikazu; Aoki, Kotaro; Yagi, Shintaro; Maeda, Tadashi; Miyazaki, Taito; Yoshizawa, Sadako; Aoyagi, Katsumi; Tateda, Kazuhiro
Abstract: We evaluated the rapid immunochromatographic test for severe acute respiratory coronavirus 2 (SARS-CoV-2) antigen detection using 16 saliva specimens collected from 6 COVID-19 hospitalized patients, and detected N-antigen in 4 of 7 RT-PCR positive specimens. This POCT detected SARS-CoV-2 antigen in saliva and would be useful for COVID-19 diagnosis.